Les archives en milieu muséal: le cas du Musée McCord - Cartier, François (Archives, 2005)
Keywords: Archives; Musée McCord; Musées

Le McCord: l'histoire d'un musée universitaire, 1921-1996 - Young, Brian (Cahiers du Québec, 2001)
Keywords: Musée McCord; Musées

Cliquer sur l’histoire - Larouche, Marie-Claude (Continuité, 2004)
Keywords: Musée McCord; Musées

The Making and Unmaking of a University Museum: the McCord, 1921-1996 - Young, Brian J. (McGill-Queen's University Press, 2000)
Keywords: McCord (famille); McCord, David Ross; Musée McCord; Musées

Location, Location, Location: David Ross McCord and the Makings of Canadian History - Harvey, Katryn (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
Keywords: McCord (famille); McCord, David Ross; Musée McCord; Musées

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord, David Ross; Musée McCord; Musées

Suspended conversations: the afterlife of memory in photographic albums - Langford, Martha (McGill-Queen's University Press, 2008)
Keywords: Musée McCord; Musées; Photographie

Témoignages autochtones - McCaffrey, Maria T. (Continuité, 2002)
Keywords: Autochtones; Expositions; Musée McCord; Musées

First Nations, Museums and McCord Museum's Journey Across Borders - Jarosova, Marketa (Université Concordia, 2001)
Keywords: Autochtones; Expositions; Musée McCord; Musées

"Bonnie Lassies" and a "Coat of Many Colours": Highland-Inspired Clothing at the McCord Museum - Stack, Eileen (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Musée McCord; Musées; Vêtements; Écossais

Le projet de sauvegarde de la collection Bens Delicatessen. Bien plus que les archives du smoked meat! - Cartier, François (Archives, 2008)
Keywords: Archives; Confédération des syndicats nationaux; Musée McCord; Musées; Restaurant

Montréal, 1701: Planting the Tree of Peace - Havard, Gilles (Signes des Amériques, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

Montréal, 1701: planter l'arbre de paix - Havard, Gilles (Signes des Amériques, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

The Scots of Montreal: a pictorial album - Marrelli, Nancy; Dardick, Simon (Véhicule Press, Musée McCord et St. Andrew's Society of Montreal, 2005)
Keywords: Écossais

Deux quotidiens se rencontrent. Le regard de l'historien - Burgess, Joanne; Lauzon, Gilles (Exposition virtuelle: Deux quotidiens se rencontrent, 2002)
Keywords: Notman, William; Photographie

Le lait: une question de vie et de mort - Burgess, Joanne (Clés pour l’histoire: circuits thématiques, 2004)
Keywords: Alimentation; Mortalité

Montréal, métropole du Canada, 1896-1914 - Linteau, Paul-André (Clés pour l’histoire: circuits thématiques, 2004)
Keywords: Métropole

Montréal, ville industrielle, 1850-1896 - Linteau, Paul-André (Clés pour l’histoire: circuits thématiques, 2004)